Managing up how to forge an effective relationship with those above you - Badowski, Rosanne (New York Currency, 2003)
Everyone has a boss. And anyone who has aspired to move up the corporate ladder knows that their relationship with those they report to is crucial. In Managing Up Rosanne Badowski offers a straightforward, entertaining, no-holds-barred account of what it takes to make your relationship with your boss work to your advantage, no matter where you stand in the corporate hierarchy.
Includes bibliographical references and index.
Keywords: Welch, Jack, 1935-